Выбор оптимальных речевых кодеков с учетом совокупности показателей качества методом анализа иерархий - (:unkn) unknown (ХНУРЕ, 2009)
In article the consideration theoretical and practical features of application of a method of the analysis of hierarchies for a choice of the speech codec, optimum on set of indicators of quality.
Keywords: Метод анализа иерархии; речевой кодек